Front Cover: Syntheses and Crystal Structures of Two Cadmium Methanetetrabenzoates Featured by Open Framework and Infinite Layers (Z. Anorg. Allg. Chem. 14/2019) - Harms, Sven; Köferstein, Roberto; Görls, Helmar; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2019)
The cover picture shows coordination polymers with the anion of methanetetrabenzoic acid (MTB) featuring tetrahedrally directed functional groups, which will favour frameworks related to the structure of diamond often being called diamondoid. If interpenetrating structures are avoided, these frameworks will provide voids able to accomodate guest molecules. A natural analogue is known with the mineral melanophlogite. Cd2[µ8‐MTB]·3H2O·DMF (1) has channel‐like voids of 670 pm x 360 pm diameter, which accomodate water molecules and DMF. In [Cd4(2,2'‐bipy)4(µ7‐MTB)2]·7DMF (2) a coligand is used, preventing formation of a three‐dimensionally polymeric framework. However, the layers of 2 stacked in …AA… sequence have small openings of 340 pm x 320 pm width. More details are discussed in the article by S. Harms, R. Köferstein, H. Görls, and C. Robl on page 912.